Eliminating human poverty: macroeconomic & social policies for equitable growth - Mehrotra, S. Santosh Mehrotra; Delamonica, E. Enrique Delamonica (New Jersey, Zed Books., 2007)
This examination of how basic social services, particularly education, health and water, can be financed and delivered more effectively departs from the dominant macro-economic paradigm. Drawing on their own broad-ranging research at UNICEF and UNDP, the authors argue that fiscal, monetary, and other macro-economic policies for poverty reduction, human development and economic growth can be compatible with micro-level interventions to provide basic social services. Policymakers have more flexibility than is usually assumed to engage in macro-economic and growth-oriented policies that can also expand human capabilities and fulfill human rights. More than just more aid is needed. Strategic shifts in aid policy, decentralized governance, health and education and the private-public mix in service provision are a prerequisite to achieve the goals of human development and to eliminate human poverty within a generation.
Includes bibliography references
Keywords: Eliminating human poverty